2008
DOI: 10.1002/j.0022-0337.2008.72.1.tb04456.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Decision Making in Restorative Dentistry, Endodontics, and Antibiotic Prescription

Abstract: The purpose of this study was to evaluate the influence of geographic location of graduation (Israel, Eastern Europe, Latin America) on decision making regarding management of dental caries, periapical lesions, and antibiotic prescribing routines. A questionnaire was given to ninety-eight general practitioners regarding demographic and work habits. Photographs of lesions were shown on a screen. Participants reported recommended treatment and whether they would routinely prescribe antibiotics following regular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 36 publications
3
19
0
Order By: Relevance
“…Antibiotic resistance patterns might vary according to geographic locations. Zadik & Levin () evaluated the influence of geographic locations (Israel, Eastern Europe, Latin America) on decision‐making regarding management of dental caries, periapical lesions and antibiotic prescribing routines. Latin American graduates prescribed more antibiotics following endodontic treatment and retreatment.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic resistance patterns might vary according to geographic locations. Zadik & Levin () evaluated the influence of geographic locations (Israel, Eastern Europe, Latin America) on decision‐making regarding management of dental caries, periapical lesions and antibiotic prescribing routines. Latin American graduates prescribed more antibiotics following endodontic treatment and retreatment.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of doctors of dental medicine accounts for 7.41% of the overall consumption of antibiotics in Croatia, while the usage of these drugs in hospitals is about 10% (14). Research performed in other countries showed that there is a general trend towards overprescribing (6,10,(15)(16)(17)(18) of antibiotics in dental community, which can significantly contribute to the worldwide problem of bacterial resistance. Although the development of bacterial resistance is not in a simple quantitative relationship with the volume of the drug, the reduction in antibiotic resistance can only occur after a significant reduction in antibiotic use (7).…”
Section: Discussionmentioning
confidence: 99%
“…isuse of antibiotics has given rise to the growing problem of antibiotic resistance. [1][2][3] Even when antibiotics are used correctly, there can be problems because past antibiotic use can be linked to a person's developing resistant microbes. [4][5][6] Therefore, the decision to prescribe an antibiotic is important, and the potential positive results must be weighed against the potential negative consequences.…”
mentioning
confidence: 99%